2016
DOI: 10.1136/postgradmedj-2015-133454
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fracture risk in osteoporosis: the use of fracture prediction tools in an osteoporosis clinic population

Abstract: The calculated 10 year risk for MO fracture between FRAX and QFracture was similar, whereas that of HI fracture was significantly different. The agreement to treatment between QFracture-20/3 and FRAX-NOGG was only 45%. Treatment decisions can differ depending on the fracture calculation tool used when coupled with certain intervention thresholds or guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Over the past decade, researchers have attempted to develop easy and efficient assessment tools for the early screening of osteoporosis, but these have not been validated for the use in Asian populations. 6,7 The osteoporosis self-assessment tool for Asians (OSTA), established using a multinational Asian cohort, was developed to identify patients with a high osteoporosis risk by considering body weight and age only. 8,9 Studies demonstrated that OSTA could help to predict fracture risk among postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, researchers have attempted to develop easy and efficient assessment tools for the early screening of osteoporosis, but these have not been validated for the use in Asian populations. 6,7 The osteoporosis self-assessment tool for Asians (OSTA), established using a multinational Asian cohort, was developed to identify patients with a high osteoporosis risk by considering body weight and age only. 8,9 Studies demonstrated that OSTA could help to predict fracture risk among postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…This has been described in other cohorts but not as yet in elderly fallers who are a group with high need for accurate fracture risk prediction. [30][31][32] Indeed, individuals over 70 years make up a large and important cohort, with an exceedingly high falls incidence of 42%. 33 The primary objective of this study was to investigate the novel question of how these risk calculators might diverge in their prediction of fracture risk in elderly fallers.…”
Section: Summary and Aimsmentioning
confidence: 99%
“…A number of studies have investigated the seasonal variation in OP presentation, and suggested that the seasonal variation in vitamin D concentration may be relevant to the occurrence of OP [29][30][31][32]. In a Greek cohort of 596 postmenopausal women with OP, there was a seasonal variation in serum levels of 25-hydroxy vitamin D [25(OH)D], with the highest and lowest 25(OH)D levels noted in late summer/early autumn months (August/September/October) and late winter/early spring months (March), respectively.…”
Section: Principal Findingsmentioning
confidence: 99%